2007
DOI: 10.18388/abp.2007_3224
|View full text |Cite
|
Sign up to set email alerts
|

Multicellular behaviour and production of a wide variety of toxic substances support usage of Bacillus subtilis as a powerful biocontrol agent.

Abstract: Intensive cultivation of plants in the monoculture field system in order to feed the continuously growing human population creates a need for their protection from the variety of natural competitors such as: bacteria, fungi, insects as well as other plants. The increase in the use of chemical substances in the 20th century has brought many effective solutions for the agriculture. However, it was extremely difficult to obtain a substance, which would be directed solely against a specific plant pathogen and woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
1
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(94 citation statements)
references
References 106 publications
(149 reference statements)
1
79
1
8
Order By: Relevance
“…Bacillus subtilis, and other members of the genus Bacillus, have long been used as BCAs in agriculture (Nagorska et al, 2007;Ongena and Jacques, 2008). For example, several B. subtilis strains have been successfully employed in pest and disease management programmes (Wulff et al, 2002;Bais et al, 2004;Stein, 2005;Lemessa and Zeller, 2007;Nagorska et al, 2007;Ji et al, 2008;Ongena and Jacques, 2008;Chen et al, 2009a,b). In this work, we isolated wild strains of B. subtilis that demonstrated strong biocontrol activities towards a number of fungal pathogens and a soil-borne bacterial pathogen R. solanacearum in both in vitro assays and experiments performed under greenhouse conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacillus subtilis, and other members of the genus Bacillus, have long been used as BCAs in agriculture (Nagorska et al, 2007;Ongena and Jacques, 2008). For example, several B. subtilis strains have been successfully employed in pest and disease management programmes (Wulff et al, 2002;Bais et al, 2004;Stein, 2005;Lemessa and Zeller, 2007;Nagorska et al, 2007;Ji et al, 2008;Ongena and Jacques, 2008;Chen et al, 2009a,b). In this work, we isolated wild strains of B. subtilis that demonstrated strong biocontrol activities towards a number of fungal pathogens and a soil-borne bacterial pathogen R. solanacearum in both in vitro assays and experiments performed under greenhouse conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore expanded our focus to include the production of antimicrobial agents. Bacillus species produce a variety of antimicrobial agents that were proposed to be important in plant biocontrol since these molecules could inhibit growth of certain pathogenic soil microorganisms (Bais et al, 2004;Stein, 2005;Nagorska et al, 2007). To test antimicrobial activities in our wild isolates, we performed in vitro plate assays for the antagonistic activities of the 20 wild strains (from CYBS-1 to CYBS-20) towards nine different plant pathogens (Table 2).…”
Section: Antimicrobial Activities Are Also Important For Plant Protecmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of the Bacillus genus have long been used as BCAs to control plant diseases (Fravel, 2005;Nagorska et al, 2007;Ongena and Jacques, 2008). These bacteria produce a variety of antimicrobial cyclic lipopeptides (LPs), including iturins, fengycins and surfactins (Phae et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus subtilis is a widespread Gram-positive bacterium, which is non-toxic and harmless to humans, animals and the environment. Many studies have shown that B. subtilis has a close relationship with plants, with the ability to promote plant growth Manjula & Podile 2005;Singh et al 2008;Swain & Ray 2009) and protect plants from pests (Nagó rska et al 2007;Abeysinghe 2009). As growth-promoting endophytic bacteria, some strains of B. subtilis have a synergistic effect on Rhizobiummediated nodulation and nitrogen fixation (Yoshida et al 2006;Rinu & Pandey 2009).…”
Section: Introductionmentioning
confidence: 99%